Agricultural science teachers proficiency in entrepreneurship development - Abdulmumini, Umar; Ayodele, Oguntunde Gabriel; Man, Norsida (Faculty of Technology Education, Abubakar Tafawa Balewa University Bauchi, 2020)
This study was carried out to determine Agricultural Science Teachers’ proficiency in entrepreneurship development of Senior Secondary School Students in Gombe State, Nigeria. Survey research design was adopted for the study. The target population of this study was made up 700 urban Agricultural Science teachers and 500 rural Agricultural Science teachers all from Senior Secondary Schools in Gombe State, Nigeria, making a population size of 1200 urban and rural Agricultural Science teachers. Purposive stratified random sampling techniques was used to obtained 1000 respondents made up of 500 rural Agricultural Science teachers and 500 urban Agricultural Science teachers as well. The instrument for collecting data was structured questionnaire which was developed by the researchers for the study. The questionnaire was made up of 32 items which were arranged in accordance with the research questions. The instrument was subjected to content and face validity by three experts. Data collected were analyzed using mean and standard deviation for research questions 1-6, decision rule of 2.50 was used. The findings revealed that Agricultural Science teachers are not proficient in developing innovation, entrepreneurial creativity, new venture creation as well as identification of investment opportunity in agriculture, but they are proficient in determination of capital requirement in Agriculture and also aware of agribusiness ownership in Agriculture.